Keragaman dan Kelimpahan Populasi Parasitoid Telur Penggerek Batang Padi di Kabupaten Tabanan - NI MADE SUWARTINI; I WAYAN SUSILA; A.A. AYU AGUNG SRI SUNARI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2017)
The Diversity and Abundance of Egg Parasitoid Population Rice Stem Borer in Tabanan Regency Rice is the staple food for most of the population of Indonesia. Tabanan Regency is a center production of rice in Bali Province. Judging from rice production in 2009 Tabanan Regency can produce 242 thousand tons of grain per year, but to improve production of rice in the field has many obstacles, one of them is rice stem borer pest. Rice stem borer can attack plants in the vegetative phase and the generative phase. It is necessary for the proper control measures, through the concept of integrated pest management that emphasizes biological control efforts that use natural enemies. Biological control by using egg parasitoid rated excellent because do not cause resistance and resurgence, organisms that are used to find the host, can multiply and spread, and control can be run by itself. Egg parasitoid of rice stem borer is an important factor that can regulate the population of rice stem borer pest abundance in the field. There were three types of rice stem borer egg parasitoids in Tabanan Regency are Trichogramma japonicum Ashm, Telenomus rowani Gahan, and Tetratichus schoenobii Ferr. Parasitoid of T. japonicum is dominant parasitoids and parasitization rate of this highest than the other parasitoids at each altitude. The diversity of rice stem borer egg parasitoid relatively low at <1.5. The highest population abundance indicated by T. japonicum ( 33.8 % ) at height <250 ( 0-250 ) masl ( meters above sea level ) and the lowest was in the height of T. rowani >500( 500-750 ) masl.